IN VITRO AND IN VIVO ANTI-TRYPANOSOMAL ACTIVITIES OF METHANOL EXTRACT OF AZADIRACHTA INDICA STEM-BARK - Wanzala, Everlyne N.; Gikonyo, Nicholas K.; Murilla, Grace; Githua, Mercy; Hassanali, Ahmed (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Current chemotherapeutic agents for the treatment of African trypanosomiasis have become largely ineffective, necessitating the search for alternative compounds. The objective of this study was to evaluate in vitro anti-trypanosomal activities of methanol extracts of parts of Azadirachta indica against Trypanosoma brucei rhodesiense, Trypanosoma brucei brucei and Trypanosoma evansi and establish the in vivo efficacy of the most active extract.Materials and methods: Maceration of powdered leaves, stem bark and root bark of the plant in methanol afforded three extracts. In vitro assays were carried out with the extracts on the three trypanosome strains in 96-well microtitre plates at concentration ranges of 4000 - 1000μg/ml. The most active extract was assayed in vivo using Trypanosoma brucei rhodesiense infected Swiss albino mice at doses of 100, 200 and 400 mg/kg body weight. Melarsoprol and suramin served as positive controls. The infected untreated group served as the negative control. Parasitaemia levels, packed cell volume, body weight changes and mean survival period of all groups were monitored throughout the experimental period.Results: Methanol extract of the stem bark of A.indica was most active in vitro against all the three trypanosome strains (MIC values of 9.93±1.88, 16.25±0.92 and 9.97±0.44μg/ml for T. b. rhodesiense, T. b. brucei and T. evansi, respectively). The extract showed optimum activity at 400 mg/kg and was comparable to the positive control groups. Parasitaemia levels were kept at a significantly low level (p < 0.05) by the extract compared to the negative control. Notably, there was no significant difference (p>0.05) in mean survival time of mice treated with the extract at 400 mg/kg and the positive controls.Conclusion: In vitro and in vivo anti-trypanosomal activities of the methanol extract of A. indica stem bark could be attributed to the presence of constituents of moderate polarity.